RELOKASI PEDAGANG PASAR TRADISIONAL SIBUHUAN (2013-2018) - AHMAD SUKRI HARAHAP (Jurnal TAROMBO, 2019)
ABSTRACT This study examines the relocation policy of Sibuhuan traditional market traders in Sibuhuan village market in Padang Lawas district from 2013 to 2018. And this study aims to describe and analyze the history of sibuhuan traditional market traders relocation policy, factors that encourage traders in rejection activities, the impacts experienced Sibuhuan traditional market traders Padang lawas district. This study uses historical research methods, and this study includes qualitative research which includes four research steps, namely: 1. Heuristics, the source gathering stage, 2. Source criticism, the stage for testing the source, 3. Interpretation, interpretation, 4. Historiography, the writing stage . The results of this study show that the history of the establishment of the Sibuhuan traditional market and the background of the emergence of the relocation policy initiated by the Padang Padang district government with the CV CV Martua developers who were rejected by traders, the traders felt that the relocation plan would harm them because of the market location which they will occupy is very quiet / lonely not strategic besides that the market distance is too far. In 2013 as an initial limitation, since the inauguration of the new market began by the old Padang district head H Ali Sutan Harahap as well as planning and implementing the location of new market traders. The year 2018 was chosen as the final frontier, because with the start of the discussion about the relocation of traders to new markets, leaving the new market buildings unused and unmanageed which were overgrown with shrubs. The factor that encourages the relocation of sibuhuan traditional market traders is the development factor where the location of the old market is right in the heart / core of the city where this location also includes the trans-Sumatra route (riau) so that it can interfere or hinder development and transportation. Keywords: Traders, Markets, Relocation.